Effect of vasopressin and methylprednisolone vs. placebo on long-term outcomes in patients with in-hospital cardiac arrest a randomized clinical trial. (June 2022) - Granfeldt, Asger; Sindberg, Birthe; Isbye, Dan; Kjærgaard, Jesper; Kristensen, Camilla M.; Darling, Søren; Zwisler, Stine T.; Fisker, Stine; Schmidt, Jens Christian; Kirkegaard, Hans; Grejs, Anders M.; Rossau, Jørgen R.G.; et al.
Abstract: Objective: The primary results from the Vasopressin and Methylprednisolone for In-Hospital Cardiac Arrest (VAM-IHCA) trial have previously been reported. The objective of the current manuscript is to report long-term outcomes. Methods: The VAM-IHCA trial was a multicenter, randomized, double-blind, placebo-controlled trial conducted at ten hospitals in Denmark. Adult patients (age ≥ 18 years) were eligible for the trial if they had an in-hospital cardiac arrest and received at least one dose of epinephrine during resuscitation. The trial drugs consisted of 40 mg methylprednisolone (Solu-Medrol®, Pfizer) and 20 IU of vasopressin (Empressin®, Amomed Pharma GmbH) given as soon as possible after the first dose of epinephrine. This manuscript report outcomes at 6 months and 1 year including survival, survival with favorable neurological outcome, and health-related quality of life. Results: 501 patients were included in the analysis. At 1 year, 15 patients (6.3%) in the intervention group and 22 patients (8.3%) in the placebo group were alive corresponding to a risk ratio of 0.76 (95% CI, 0.41–1.41). A favorable neurologic outcome at 1 year, based on the Cerebral Performance Category score, was observed in 14 patients (5.9%) in the intervention group and 20 patients (7.6%) in the placebo group (risk ratio, 0.78 [95% CI, 0.41–1.49]. No differences existed between groups for favorable neurological outcome and health-related quality of life at either 6 months or 1 year. Conclusions: Administration of vasopressin and methylprednisolone, compared with placebo, in patients with in-hospital cardiac arrest did not improve long-term outcomes in this trial.